Modification of excitation-contraction coupling by 4-chloro-m-cresol in voltage-clamped cut muscle fibres of the frog (R. pipiens) - Struk, A (Blackwell Science Inc, 1999)
1. The effect of 5 μm 4-chloro-m-cresol (4-CmC) on voltage-controlled Ca(2+) release was studied in cut muscle fibres of the frog loaded with internal solutions containing 15 mM EGTA. Fibres were voltage clamped using a double Vaseline gap system, and Ca(2+) signals were recorded with the fluorescent indicator dye fura-2. 2. Resting intracellular free Ca(2+) concentration increased from 61 to 100 nm upon application of 4-CmC. 3. Both peak rate of release of intracellularly stored Ca(2+) and the steady level attained after 50 ms of depolarization increased, but the potentiation of the latter was more pronounced (by a factor of 1.7 versus 1.3). The voltage of half-maximal activation remained unchanged. 4. Non-linear intramembranous charge movements showed no significant change in voltage dependence while the maximal charge displaced by depolarization increased by 25%. 5. The dependence of peak release flux on total intramembranous charge was not different in 4-CmC, but for the steady level of release the steepness of the relation increased by a factor of 1.3. 6. The stimulating effect of 5 μm 4-CmC on depolarization-induced Ca(2+) release resembled the potentiation by 0.5 mm caffeine. However, 0.5 mm caffeine increased the peak and steady levels of the release rate by a similar factor and caused no increase in the resting free calcium concentration, indicating different modes of action of the two substances. 7. Neither 5 μm 4-CmC nor 0.5 mm caffeine led to a loss of voltage control of Ca(2+) release during repolarization after short depolarizations, as has been reported previously for caffeine. Potentiated Ca(2+) release could be terminated by repolarization as fast as under control conditions both with 15 mm and 0.1 mm internal EGTA. 8. The effects of 4-CmC may result from a direct opening of the release channel combined with an enhancement of the transduction mechanism that couples channel opening to displacement of voltage sensor charges.